Aplikasi Pelaporan dan Monitoring Data Limbah B3 Pada Tempat Penyimpanan Sementara Berbasis Web di PT. PLN (Persero) Sektor Pengendalian Pembangkitan Bandar Lampung - Ade Irma Rilyani; Imam Asrowardi; Kurniawan Saputra (P3M Politeknik Negeri Bengkalis, 2018)
Abstrack - PT. PLN (Persero) Sektor Pengendalian Pembangkitan Bandar Lampung has powerhouse unit that produces B3 waste (hazardous and toxic substance). This company has a job to keep the environment from production impact that was produced by managing B3 waste that was created by every single powerhouse unit. K3L sector office staff and LK2 powerhouse unit staff face difficulties in doing the data reporting process and monitoring of B3 waste that is done by directly visiting sector office and powerhouse unit due to the distance that should be taken is quire far and takes a long time. The purpose of this final project is to create a web-based B3 waste data reporting and monitoring application to ease the reporting process and monitoring B3 waste data. The method that is used in this final project is Rapid Application Development (RAD) with the stages of requirement planning, user design, construction and cutover. Keywords - application, B3 waste, monitoring, reporting.